THE IMPACT OF THE BUDGETARY COMPONENT OF FISCAL POLICY ON MACROECONOMIC GROWTH IN CONDITIONS OF FINANCIAL DECENTRALIZATION: CASE OF UKRAINE - O. A. Shevchuk; V. V. Martynenko (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
The article examines the role of the budget component of Ukraine’s fiscal policy in macroeconomic growth. The directions of increase of economic growth under the influence of financial decentralization are offered. The expediency of using multifactor economic and mathematical modelling in the study of the dynamics of the national accounts of Ukraine under the influence of indicators of the budget component of fiscal policy is substantiated.